Three Cases of Arteritic Anterior Optic Neuropathy Several Months after COVID-19 Vaccination - Yuichi Yamamoto; Ken Ogino; Satoshi Yasuhara; Yu Kawashima; Toshiya Miki (Case Reports in Ophthalmological Medicine)
Background. Vaccines have been approved worldwide to control the coronavirus disease-19 (COVID-19). However, the postvaccination side effects remain controversial. Here, we describe three Japanese cases of arteritic anterior ischaemic optic neuropathy (AAION) following COVID-19 vaccination. Case presentation. The first case involved an 87-year-old woman who presented with vision loss in the right eye 2 months after her second COVID-19 vaccine and in the left eye 2 days later. The second case involved an 88-year-old woman who presented with vision loss in both eyes 3 months after receiving a second vaccine. The third case involved an 80-year-old man who presented with vision loss in the right eye 5 months after receiving a second vaccine. The C-reactive protein level and erythrocyte sedimentation rate were elevated in all patients. Biopsy of the temporal artery or auricular cartilage showed arteritic occlusion in case 2 and polychondritis in case 3. These patients were referred to a local Japanese hospital in 2021 over a period of no longer than 3 months. Conclusion. We observed three cases of AAION after the affected individuals received their second COVID-19 vaccine. Further long-term investigations of ophthalmological events after COVID-19 vaccination are warranted.